Social psychology of emotion - Ellis, Darren; Tucker, Ian (Los Angeles Sage, 2015)
The study of emotion tends to breach traditional academic boundaries. It requires multi-modal perspectives and the suspension of dualistic conventions to appreciate its complexity. This book analyses historical, philosophical, psychological, biological, sociological, post-structural, and technological perspectives of emotion that Ellis and Tucker argue are important for a viable social psychology of emotion. It begins with early ancient philosophical conceptualisations of pathos and ends with analytical discussions of the transmission of affect which permeate the digital revolution. It will be of interest to upper level undergraduate and postgraduate students of psychosocial studies, the individual and society, and courses across the social sciences dealing with affect and emotion.-- Source other than the Library of Congress.
Machine generated contents note: Social psychology, emotion and interdisciplinarity -- Chapter Summaries -- 1. Two Ancient Theories of Emotion: Plato and Aristotle -- Key aims -- Introduction -- Plato -- A dualistic split -- A tripartite division -- An emerging blurred division -- Plato's psychosocial studies of emotion -- Higher emotion -- Aristotle -- The powers of De Anima -- Passive passions -- Emotion and virtue -- Aristotle's psychosocial studies of emotion -- Conclusion -- Further reading -- 2. Hellenistic and Medieval Theologies of Emotion -- Key aims -- Introduction -- The Hellenistic period -- Early Stoa -- Middle Stoa -- Late Stoa -- Epicureanism -- Augustine -- Passion, affection and the will -- The golden age of Islam -- Poetic evocations -- Aquinas -- The passions of the soul -- The virtues -- Conclusion -- Further reading -- 3. Enlightenment Philosophies of Emotion -- Key aims -- Introduction -- Descartes' little gland -- The bio-social factors -- Spinoza and affectus -- Conatus -- A dual-aspect monism -- Affective change -- Hume and moral sentimentalism -- Hobbes and fear -- Post-scepticism -- Hume's psychology -- The association of ideas -- Reason enslaved to passion -- Sympathy and the psychosocial -- Kant's synthetic a priori -- The rational being -- Sympathy's infection -- Affects and passions -- Social passions -- Conclusion -- Further reading -- 4. The Role of Emotion In The Development of Social Psychology As A Discipline -- Key aims -- Introduction -- The `peculiar vividness of feeling' -- Evolutionary psychology -- William James' emotional `mind stuff' -- Walter Cannon's emotional thalamus -- The classification of emotion -- William McDougall's introduction to social psychology -- Pseudo-instincts -- Lewin -- Conclusion -- Further reading -- 5. Group Psychology and Emotion -- Key aims -- Introduction -- Freud's drive theory -- Affect and idea -- Freud's group psychology -- Libidinal ties -- The pathologisation of the crowd -- Deindividuation -- Social norm theory -- Social identity theory -- Primitive emotional contagion -- Primitive emotion -- Asocial theory -- Virality and contagion -- Tarde -- Somnambulism -- Post-Freudian groups -- Bion's basic assumptions -- Foulkes' psychosocial theorisation -- Conclusion -- Further reading -- 6. Biological Understandings of Emotion -- Key aims -- Introduction -- Darwin's expressions -- The universality thesis -- Natural selection, habits and instincts -- Darwin's determinism -- Neo-Darwinism -- The triune brain -- LeDoux's amygdale -- Triune critiques -- Hemispheric distinctions -- Split brain -- Cultural factors -- Affective neuroscience -- Empathic mirroring -- Neuropsychoanalysis -- Damasio's somatic marker hypothesis -- Conclusion -- Further reading -- 7. Sociological Understandings of Emotion -- Key aims -- Introduction -- A two factor model -- The dramaturgical theory of emotion -- Face-work -- Feeling rules -- Emotion work -- The constructions of gendered emotion -- Gendered assumptions -- The subordination hypothesis -- Sexual desire and emotional connectedness -- Conclusion -- Further reading -- 8. Emotion Talk: Theories and Analysis -- Key aims -- Introduction -- Emotional disclosure -- Inhibition confrontation -- Cognitive reappraisal -- The multiple code theory -- Referential activity -- Content analysis of emotion -- Discourse analysis of emotion -- Combining methods -- Incongruent rationalisation -- Conclusion -- Further reading -- 9. Affect Theory: Post-Structuralist Accounts -- Key aims -- Introduction -- Affect theory -- Affect in Tomkins -- Affect in Deleuze -- Actual selection -- Affect in Massumi -- Affect and subjectivity -- Conclusion -- Further reading -- 10. Digital Emotion -- Key aims -- Introduction -- Simondon's technics -- Affective collective baggage -- Techno-biological emotion -- Further reading.
Includes bibliographical references (pages [183]-193) and index.
Keywords: Emotions; Social psychology